Compressing random microstructures via stochastic Wang tilings - Novák, Jan; Kučerová, Anna; Zeman, Jan (Physical review. E, Statistical, nonlinear, and soft matter physics, 2012)
This Rapid Communication presents a stochastic Wang tiling-based technique to compress or reconstruct disordered microstructures on the basis of given spatial statistics. Unlike the existing approaches based on a single unit cell, it utilizes a finite set of tiles assembled by a stochastic tiling algorithm, thereby allowing to accurately reproduce long-range orientation orders in a computationally efficient manner. Although the basic features of the method are demonstrated for a two-dimensional particulate suspension, the present framework is fully extensible to generic multidimensional media.
Keywords: Imaging, Three-Dimensional; algoritmy; komprese dat; testování materiálů; reprodukovatelnost výsledků; biofyzika; statistické modely; Data Compression; Models, Statistical; zobrazování trojrozměrné; Stochastic Processes; Reproducibility of Results; Algorithms; Biophysics; stochastické procesy; počítačové zpracování obrazu; Materials Testing; Image Processing, Computer-Assisted